2020
DOI: 10.3390/w12113200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of the Interaction between Common Metal Ions and Humic Acids

Abstract: Humic acids (HAs) have important environmental and geochemical effects on soil, water environments and sediment. HAs strongly complex some metal ions, which affects the migration of metal ions and the colloidal aggregation of HA. Here, the complexation of Ca2+ and Mg2+ with HA in aqueous solution under neutral conditions has been systematically studied by molecular dynamics (MD) simulation. The results show that the aggregation of HA is caused by the complexation of HA and metal ions, mainly due to the intermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Even in the presence of inorganic cations with the same valency, it was reported that the strength of HA aggregates was higher in the presence of Ca 2+ than for Mg 2+ , which is consistent with higher efficiency of HA coagulation with a cation of a larger ionic radius and the same valency . Such a comparison was further confirmed by an MD simulation study, which clarified the monodentate and bidentate coordination between Ca 2+ and carboxylate groups among the complexation of HA and cationic ions, while for Mg 2+ , only monodentate coordination was found …”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Even in the presence of inorganic cations with the same valency, it was reported that the strength of HA aggregates was higher in the presence of Ca 2+ than for Mg 2+ , which is consistent with higher efficiency of HA coagulation with a cation of a larger ionic radius and the same valency . Such a comparison was further confirmed by an MD simulation study, which clarified the monodentate and bidentate coordination between Ca 2+ and carboxylate groups among the complexation of HA and cationic ions, while for Mg 2+ , only monodentate coordination was found …”
Section: Introductionsupporting
confidence: 55%
“…35 Such a comparison was further confirmed by an MD simulation study, which clarified the monodentate and bidentate coordination between Ca 2+ and carboxylate groups among the complexation of HA and cationic ions, while for Mg 2+ , only monodentate coordination was found. 36 As Ca 2+ ions are omnipresent in raw water and often become added in the form of lime during the water treatment process, a large number of studies have been dedicated to elucidating the Ca 2+ effect within the conventional water treatment process. For instance, it has been found that the consumption of aluminum sulfate (Al 2 (SO4) 3 ) was sufficiently reduced by around 20% to achieve comparable removal efficiency at pH above 6 when adopting CaCl 2 as a cocoagulant to remove NOM from raw water.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The angle change of the surfactant hydrophobic tail chain and hydrophilic head group characterizes the interaction strength between the surfactant and the talcum powder surface. Also, it reflects the degree of stretching of the surfactant molecule (Wu et al, 2021). The larger the surfactant angle, the stronger the interaction between the hydrophobic tail group and the talcum powder surface, the more stable the adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular structure of the TNB molecule comprises three carboxylic (R-COOH) groups, three carbonyls (R-CO), two phenolic (R-OH) groups, two amines (R-NH 2 ), and four other alcohol groups and has a chemical composition of (C 36 H 40 O 16 N 2 ). 24 The carboxylated groups of the TNB molecule were deprotonated in the pH range of 4-9 (pK a = 4-5), whereas the phenolic (pK a = 9) and amine groups (pK a = 4.6) were in a protonated state. 25 Five such molecules of TNB were distributed randomly over the simulation box of size 9 × 9 × 9 nm 3 , with the PSslab being at its center, as shown in Fig.…”
Section: Simulationsmentioning
confidence: 99%